A fundamental test for stellar feedback recipes in galaxy simulations - Fujimoto, Yusuke; Chevance, Mélanie; Haydon, Daniel T.; Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. Direct comparisons between galaxy simulations and observations that both reach scales ≲100 pc are strong tools to investigate the cloud-scale physics
Gesehen am 26.06.2019